Oncogenic reg IV is a novel prognostic marker for glioma patient survival - Wang Qi; Deng Jianping; Yuan Jun; Wang Liang; Zhao Zhenwei; He Shiming; Zhang Yongsheng; Tu Yanyang (BMC, 2012)
Abstract Aim The aberrant expression of regenerating islet-derived family member, 4 (Reg IV) has been found in various human cancers. However, the roles of Reg IV gene and its encoding product in human glioma have not been clearly understood. Therefore, the aim of this study was to investigate the clinicopathological significance of Reg IV expression in glioma. Methods Reg IV mRNA and protein expression in human gliomas and non-neoplastic brain tissues were respectively detected by real-time quantitative RT-PCR assay, Western blot, and immunohistochemistry. The association of Reg IV immunostaining with clinicopathological factors and prognosis of glioma patients was also statistically analyzed. Results Reg IV mRNA and protein expression levels in glioma tissues were both significantly higher than those in the corresponding non-neoplastic brain tissues (both P < 0.001). Additionally, the increased Reg IV immunostaining in glioma tissues was significantly associated with advanced pathological grade (P = 0.008). Reg IV protein up-regulation was also significantly correlated with low Karnofsky performance score (KPS) (P = 0.02). Moreover, the overall survival of patients with high Reg IV protein expression was dramatically shorter than those with low Reg IV protein expression (P < 0.001). Multivariate Cox regression analysis further confirmed that Reg IV expression was an independent prognostic factor for patients with gliomas (P = 0.008). Conclusions These convinced evidences suggest for the first time that Reg IV might accelerate disease progression and act as a candidate prognostic marker for gliomas. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2145344361720706